Translating Guān'ài in the People's War on Drugs: Enacting Relations of Care in China's State-Run Methadone Maintenance Treatment Program. Issue 1 (1st March 2020) - Zhang, Chaoxiong; Song, Priscilla
Abstract: China's state-run methadone maintenance treatment (MMT) program was launched in 2003 in response to the growing HIV/AIDS epidemic and increasing criticism of compulsory rehabilitation centers. In conjunction with providing methadone replacement therapy, the Chinese state began promoting a politicized discourse of guān'ài 关爱 (care and love) as a more effective and humane method for dealing with drug users. While the medicalization of addiction as a chronic brain disease requiring long-term pharmaceutical treatment marked a watershed moment in the debate over drug control in China, the affective recasting of addiction as a social condition worthy of care is potentially even more revolutionary. But to what extent has this project transformed Chinese drug users into a legitimate target of (state) care? Based on ethnographic fieldwork conducted in Yunnan province from 2013 to 2019, we examine how various stakeholders in China's MMT program (including methadone recipients, clinicians, public health officials, police officers, and the general public) have attempted to translate the discourse of guān'ài into workable practices and relationships based on divergent understandings of how to care for and about Chinese drug users. Our analysis shows how attending to the everyday dynamics of guān'ài in the People's War on Drugs provides a novel approach to theorizing the fraught politics of care.